PC / PET material and preparation method thereof
By adding a specific proportion of toughening agent and heat stabilizer to the PC/PET composite material and using minerals treated with silane coupling agent as fillers, the problem of degradation of the material's performance during long-term thermal aging is solved, and the heat-resistant aging performance of the material is significantly improved.
Patent Information
- Application Number
- CN202411882674.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-05-09
AI Technical Summary
In the long-term thermal aging process, existing PC/PET composites are prone to molecular chain fracture and degradation products, resulting in a decline in mechanical and electrical properties, and cannot meet the application needs under high temperature and long-term stress.
PC/PET materials are prepared by using a specific proportion of toughening agent and heat stabilizer, combined with minerals treated with silane coupling agent as fillers. The material improves tensile strength by modifying minerals and improves the toughness and thermal aging properties of the material through toughening agents and thermal stabilizers.
It significantly improves the long-period thermal aging resistance of PC/PET materials, and enhances the overall performance of the material, including toughness, tensile strength and impact strength retention.
Smart Images

Figure BDA0005198573190000061 
Figure BDA0005198573190000071 
Figure BDA0005198573190000072
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite materials, and in particular to a PC / PET material and a preparation method thereof. Background Art
[0002] In the field of polymer materials, especially for applications that need to withstand high temperatures and long-term stress, such as oil-paper insulation systems, electrical equipment, aerospace, and automobile manufacturing, the thermal aging performance of materials is a crucial consideration. Although traditional materials such as insulation paper have good dielectric constants and certain mechanical properties, they have poor high temperature resistance and are easy to decompose, making it difficult to maintain stable performance for a long time in high temperature environments.
[0003] Polycarbonate (PC) and polyester film (PET) are high-performance polymer materials that are widely used in various high-end fields due to their excellent mechanical properties, electrical properties and thermal stability. However, during long-term thermal aging, PC and PET materials still face problems such as molecular chain breakage and the generation of degradation products, which leads to a gradual decline in the mechanical and electrical properties of the materials and cannot meet the application requirements under high temperature and long-term stress.
[0004] The thermal oxidation aging process of PC under conditions below the melting temperature mainly causes the breakage of the end groups and side groups. Since the ester group of PC is easier to break than the isopropyl group, the breakage of the end groups and side groups will lead to internal defects and the mechanical properties will decrease accordingly. The initial stage of degradation: In the air, due to the presence of oxygen, PC forms peroxides during degradation. The peroxides then dissociate and react with other free radicals to form aldehydes, ketones and branched products. No aldehydes or ketones were found in the degradation of PC under N2. In addition, more branched and cross-linked structure products were detected in the air, indicating that the oxygen in the air promotes the formation of branched and cross-linked structures. Since oxygen mainly affects the surface of the degradable polymer, the difference in degradation is mainly in the initial stage of degradation.
[0005] The impact strength of PC decreases significantly at the beginning of aging and after high-temperature aging, which is mainly caused by the reduction of the free volume of PC molecular chains: ① The molecular structure of PC is not completely a random coil, but a two-phase structure with a certain orderly arrangement, one of which is a long and hard fibril-like structure, and the other is a long-chain flexible structure. The two phases are staggered to form a loose network, so that there are gaps in the polymer, that is, the free volume of PC is large in the glassy state, and the structural relaxation is easy to proceed. The higher the temperature, the easier this relaxation is, and the faster the rate of conformational rearrangement is, resulting in a large decrease in the free volume fraction and the size of the gaps of PC after hot air aging and cooling, thereby reducing the impact strength. ② The PC molecular chain is forced to orient in injection molding, and an uneven molecular condensed structure is formed inside the sample. This structure undergoes molecular conformational rearrangement during the hot air aging process, but the free volume fraction and the size of the gaps remain unchanged at this time; when the hot air aged PC sample is cooled from the aging temperature to room temperature, the free volume fraction and the size of the gaps are reduced, and residual stress is generated inside the sample, which rapidly reduces the impact strength. ③ Moreover, at the beginning of hot air aging, the conformational rearrangement rate is fast and the free volume decreases sharply; the higher the aging temperature, the faster the conformational rearrangement rate and the faster the free volume decreases.
[0006] In addition, although the existing PC / PET composite materials have improved the high temperature resistance and electrical properties of the material to a certain extent, they will still degrade during the long-term thermal aging process, affecting the overall performance and service life of the material. Summary of the invention
[0007] In view of the thermal aging problem of current PC / PET composite materials, the present invention provides a PC / PET material and a preparation method thereof, which can significantly improve the long-term thermal aging resistance of the PC / PET composite material.
[0008] To achieve the above object, the embodiments of the present invention adopt the following technical solutions:
[0009] A PC / PET material and a preparation method thereof, comprising the following components by weight:
[0010] PC 45-55 copies;
[0011] PET 25-30 parts;
[0012] 13-17 parts of minerals;
[0013] Toughening agent 0.1-15 parts;
[0014] Heat stabilizer 0.1-5 parts;
[0015] Antioxidant 0.1-0.5 parts;
[0016] Lubricant 0.1-1 part;
[0017] Among them, the minerals are modified by silane coupling agent, methanol and acid solution.
[0018] Preferably, the toughening agent is one or more of a thermoplastic elastomer and a silicone toughening agent; the thermoplastic elastomer includes one or more of a polypropylene-butadiene-styrene copolymer, a polymethacrylate-butadiene-styrene copolymer, a polymethacrylate-butyl acrylate copolymer, and an ethylene-vinyl acetate copolymer.
[0019] Preferably, the heat stabilizer is one or more of phosphoric acid, trimethyl phosphate, triphenyl phosphate and triethyl phosphate; the lubricant is one or more of pentaerythritol stearate, polydimethylsiloxane and ethylene bisstearamide.
[0020] Among them, thermoplastic elastomers are materials that show rubber elasticity at room temperature and can be plasticized and formed at high temperatures. They maintain high thermal stability during processing, have high flexibility (low crystallinity) and high impact absorption performance, and achieve optimal dispersion during melt mixing with engineering thermoplastics. Silicone toughening agents are core-shell structures of organic silicon systems, with cross-linked elastomers as cores and polymers with high glass transition temperatures as shells. The core-shell particles synthesized by emulsion polymerization are controllable in size and have a narrow particle size distribution; the high glass transition temperature shell can protect the rubber from maintaining stable size during processing, which is conducive to the dispersion of particles in the matrix, and the shell of the particles has good compatibility with the matrix. The acrylic ester core-shell copolymer in the thermoplastic elastomer has a cross-linked polybutyl acrylate as the core and uses grafted polymethyl methacrylate as the shell, which makes it have high impact strength and weather resistance, uniform particle size distribution, and is not affected by mixing conditions.
[0021] Preferably, an ester exchange inhibitor is added to the heat stabilizer, and the ester exchange inhibitor is one or more of zinc phosphate, monozinc phosphate, phosphorous acid, and disodium dihydrogen pyrophosphate.
[0022] Under the condition of using acrylic core-shell copolymer, the combination of heat stabilizer and ester exchange inhibitor can passivate the active molecular chain ends of polycarbonate and polyester, inhibit the ester exchange reaction of polycarbonate polyester alloy and slow down its thermal oxidative aging, and improve the impact retention rate after thermal aging.
[0023] Preferably, the silane coupling agent is one or more of trimethoxysilane, γ-methacryloxypropyltrimethoxysilane and tetraethyl orthosilicate.
[0024] Silane coupling agent can modify the surface of mineral powder and build a "molecular bridge" between the interface of inorganic and organic substances, connecting two materials with very different properties together to improve the performance of composite materials and increase bonding strength.
[0025] Preferably, the acidic solution is a solution of a monoprotic acid, a diprotic acid or a triprotic acid with a pH value of 3 to 5. In practical use, low-cost and relatively safe monoprotic acids such as hydrochloric acid solution, acetic acid solution or benzoic acid solution are preferred.
[0026] Preferably, the mineral is a non-metallic mineral powder, including one or more of wollastonite powder, mica powder, brucite powder, heavy calcium, talc powder, and barite powder.
[0027] Under acidic conditions, silane coupling agent can modify the surface of mineral powder. The coupling agent can chemically bond with the surface of mineral powder to form a large steric hindrance, which blocks the agglomeration between the particles of mineral powder, effectively improves the compatibility with organic media, and improves its dispersion stability in organic media.
[0028] For example, the main component of talc is hydrous magnesium silicate; it contains crystal water and is easy to absorb moisture; it has a flaky structure, is relatively fluffy, has a larger specific surface area, a lower bulk density, and is easier to absorb water. The presence of silane coupling agents can increase tensile strength, change the interface of talc from hydrophilic to hydrophobic, and increase filling and dispersing properties or change the matrix properties of talc-enhanced blends.
[0029] In a second aspect, the preparation method of the above PC / PET material comprises the following steps:
[0030] The mineral is mixed with a silane coupling agent, and then a preset proportion of methanol and an acid solution are added to mix evenly, and then dried to obtain a modified mineral;
[0031] PC, PET, toughening agent, heat stabilizer, modified mineral, antioxidant and lubricant are pre-mixed, and carbon black and composite dye are added and mixed to obtain composite raw material;
[0032] The composite raw materials are melt-coextruded, cooled, blow-dried and pelletized to obtain PC / PET materials.
[0033] Preferably, the temperature of zone 2 of the twin-screw extruder is 220-240°C, the temperature of zone 3 is 230-250°C, the temperature of zone 4 is 240-260°C, the temperature of zone 5 is 235-255°C, the temperature of zone 6 is 245-265°C, the temperature of zone 7 is 245-265°C, the temperature of zone 8 is 245-265°C, the temperature of zone 9 is 245-265°C, the temperature of zone 10 is 245-265°C, and the temperature of zone 11 is 240-260°C. The composite raw material is melt-co-extruded in the extruder, the screw speed of the extruder is 450-650r / min, the residence time is 2-5min, the pre-mixing time of the high-speed mixer is 4-8min, and the re-mixing time is 5-15min.
[0034] Thirdly, PC / PET materials are used in the production of automotive interiors, communication equipment, and electronic appliances.
[0035] Advantages of the present invention: by adding a specific proportion of toughening agent and heat stabilizer, the toughness of PC / PET material is significantly improved, so that it has better resistance to long-term thermal aging. Using minerals treated with silane coupling agent as fillers significantly improves the tensile strength of the material, and changes the hydrophilicity of the minerals into hydrophobicity, increases the filling and dispersing properties, and further improves the overall performance of the material. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The raw materials used in the examples and comparative examples of the present invention are all commercially available, including but not limited to the following materials:
[0038] High viscosity PC (A1, MFR ≤ 6g / 10min): LEXAN TM PC950, LEXAN TM PC PK2870, LEXAN TM PCML3290;
[0039] Medium viscosity PC (A2, MFR ≤ 15g / 10min): LEXAN TM PC 945A-116, LEXAN TM PC 940-201;
[0040] Low viscosity PC (A3, MFR ≤ 30g / 10min): LEXAN TM PC 923A-1129, LEXAN TM PC 121R-11011;
[0041] Polyethylene terephthalate PET: CZ-318, Jiangyin Xingye;
[0042] The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased from the market.
[0043] The preparation method of the embodiment:
[0044] S1: Mix the mineral with the silane coupling agent, and then add methanol and acid solution in a preset proportion; after mixing evenly, place the treated mineral powder in an oven at 100-120°C for 20-30 hours to obtain a modified mineral.
[0045] S2: First, PC, PET, toughening agent, heat stabilizer, mineral treated with silane coupling agent, antioxidant and lubricant are mixed evenly in a high-speed mixer according to the implementation ratio for 6 minutes, and then carbon black and composite dye are added for 10 minutes to obtain a composite raw material; in this experimental scheme, the antioxidant is antioxidant 168.
[0046] S3: Add the composite raw materials into a twin-screw extruder for melt co-extrusion, the extruder temperature: 230°C for zone 2, 240°C for zone 3, 250°C for zone 4, 245°C for zone 5, 255°C for zone 6, 255°C for zone 7, 255°C for zone 8, 255°C for zone 9, 255°C for zone 10, 250°C for zone 11; the extruder screw speed is 550 rpm, and the residence time is 3 minutes. After screw extrusion, cool, blow dry, and pelletize to obtain PC / PET material.
[0047] Related performance test methods:
[0048] Bending performance: tested according to ISO 178-2010 standard, span 64mm, test rate 2mm / min.
[0049] Simple supported beam unnotched impact strength: tested according to ISO 179-1eU standard, 23℃, -30℃.
[0050] Vicat: Tested in silicone oil according to DIN ISO 306 / B 120.
[0051] Retention rate of simply supported beam unnotched impact strength: After the sample is stored at 90°C for 1000 hours, it is tested at 23°C according to ISO 179-1eU standard, and the retention rate before and after aging is calculated.
[0052] Examples 1-4 are PC / PET materials of the present invention, and the raw materials and weight parts of the examples are shown in Table 1.
[0053] Table 1: Raw materials and weight proportions of PC / PET materials in the examples
[0054] Example 1 Example 2 Example 3 Example 4 High viscosity PC / / / / Medium viscosity PC / / / / Low viscosity PC 48 45 49 45 PET 25 26 30 25 Toughening agent 10 10 2 12 Heat Stabilizer 1 3 3 2 mineral 15 15 15 15 Antioxidants 0.3 0.3 0.3 0.3 Lubricants 0.7 0.7 0.7 0.7
[0055] The performance test results of the PC / PET materials of Examples 1-4 are shown in Table 2.
[0056] Table 2: Performance test results of PC / PET materials in the examples
[0057] Example 1 Example 2 Example 3 Example 4 Bending Strength 4184 4220 4237 4210 Impact strength (23℃) 140 165 159 171 Impact strength (-30℃) 134 150 143 164 Vika 140.1 140.1 140.2 140.1 Impact strength retention rate after 1000h at 90℃ (%) 87 90 90 92
[0058] The raw materials and weight proportions of the PC / PET materials of Comparative Examples 1-9 are shown in Table 3.
[0059] Table 3: Raw materials and weight parts of PC / PET materials in comparative example
[0060]
[0061]
[0062] The performance test results of the PC / PET materials of Comparative Examples 1-9 are shown in Table 4.
[0063] Table 4: Performance test results of PC / PET materials of comparative example
[0064]
[0065] Based on the above data, Comparative Examples 1-3 did not add toughening agents and heat stabilizers, and their performance in terms of unnotched impact strength (23°C), unnotched impact strength (-30°C), Vicat, and unnotched impact strength retention rate (%) after 90°C-1000h were all weaker than those of Examples 1-4.
[0066] By comparing the data of Comparative Examples 4-6, Comparative Examples 7-9 and Examples 1-4, it can be seen that the combined use of toughening agent and heat stabilizer is significantly better than the use of toughening agent or heat stabilizer alone. The PC / PET materials of Examples 1-4 performed better than Comparative Examples 4-9 in the four tests.
[0067] By comparing the three groups of data of Comparative Examples 4-6, Comparative Examples 7-9 and Examples 1-4, it can be seen that the combined use of tougheners and heat stabilizers is significantly better than the effect of using tougheners or heat stabilizers alone. The PC / PET materials of Examples 1-4 performed better than Comparative Examples 4-9 in four tests. Among them, Example 1 added a small amount of heat stabilizer, Example 2 added a medium amount of heat stabilizer, Example 3 added a small amount of toughener, and Example 4 added a medium amount of toughener. In the bending strength test, Example 3 performed best. In the impact strength test, Example 4 had the best comprehensive test effect. In particular, in the impact strength retention test after storage at 90°C for 1000 hours, Example 4 was significantly better than the comparative example and other examples. The PC / PET material manufactured according to the method of the present application exhibited better heat aging resistance.
[0068] The advantages of the embodiments of the present invention are that by adding a specific proportion of toughening agent and heat stabilizer, the toughness of PC / PET material is significantly improved, so that it has better resistance to long-term thermal aging. At the same time, the use of minerals treated with silane coupling agents as fillers not only significantly improves the tensile strength of the material, but also converts the hydrophilicity of the minerals into hydrophobicity, enhances the filling and dispersion performance, and further improves the overall performance of the material.
[0069] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A PC / PET material and a preparation method thereof, characterized in that: By weight, it includes the following components: PC 45-55 copies; PET 25-30 parts; 13-17 parts of minerals; Toughening agent 0.1-15 parts; Heat stabilizer 0.1-5 parts; Antioxidant 0.1-0.5 parts; Lubricant 0.1-1 part; The mineral is modified by silane coupling agent, methanol and acid solution.
2. The PC / PET material according to claim 1, characterized in that: The toughening agent is one or more of a thermoplastic elastomer and a silicon-based toughening agent; the thermoplastic elastomer includes one or more of a polypropylene-butadiene-styrene copolymer, a polymethacrylate-butadiene-styrene copolymer, a polymethacrylate-butyl acrylate copolymer, and an ethylene-vinyl acetate copolymer.
3. The PC / PET material according to claim 1, characterized in that: The heat stabilizer is one or more of phosphoric acid, trimethyl phosphate, triphenyl phosphate and triethyl phosphate; the lubricant is one or more of pentaerythritol stearate, polydimethylsiloxane and ethylene bisstearamide.
4. The PC / PET material according to claim 3, characterized in that: An ester exchange inhibitor is added to the thermal stabilizer.
5. The PC / PET material according to claim 1, characterized in that: The silane coupling agent is one or more of (3-glycidyloxypropyl)trimethoxysilane, γ-methacryloxypropyltrimethoxysilane and tetraethyl orthosilicate.
6. The PC / PET material according to claim 1, characterized in that: The acidic solution is a solution of a monoprotic acid, a diprotic acid or a triprotic acid with a pH value of 3-5.
7. The PC / PET material according to claim 1, characterized in that: The mineral is a non-metallic mineral powder, including one or more of wollastonite powder, mica powder, brucite powder, heavy calcium, talc powder, and barite powder.
8. A method for preparing the PC / PET material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The mineral is mixed with a silane coupling agent, and then a preset proportion of methanol and an acid solution are added to mix evenly, and then dried to obtain a modified mineral; PC, PET, toughening agent, heat stabilizer, modified mineral, antioxidant and lubricant are pre-mixed, and carbon black and composite dye are added and mixed to obtain composite raw material; The composite raw materials are placed in a twin-screw extruder for melt co-extrusion, cooling, drying, and pelletizing to obtain PC / PET materials.
9. The preparation method according to claim 8, characterized in that: The temperature of zone 2 of the twin-screw extruder is 220-240°C, the temperature of zone 3 is 230-250°C, the temperature of zone 4 is 240-260°C, the temperature of zone 5 is 235-255°C, the temperature of zone 6 is 245-265°C, the temperature of zone 7 is 245-265°C, the temperature of zone 8 is 245-265°C, the temperature of zone 9 is 245-265°C, the temperature of zone 10 is 245-265°C, and the temperature of zone 11 is 240-260°C. The composite raw material is melt-coextruded in the extruder, the screw speed of the extruder is 450-650r / min, the residence time is 2-5min, the pre-mixing time of the high-speed mixer is 4-8min, and the re-mixing time is 5-15min.
10. Use of the PC / PET material according to any one of claims 1 to 7 in the production of automobile interiors, communication equipment, and electronic appliances.
Citation Information
Patent Citations
PC / PBT alloy material as well as preparation method and application thereof
CN104693768A
Toughened modified PC / PET alloy and preparation method thereof
CN104725810A
PC / PET composite material and product thereof
CN105838051A
Mineral reinforced PC / PET alloy resin and preparation method thereof
CN112876831A
Cited By
Bio-based high-flowability mineral reinforced PC / PET alloy material and preparation method thereof
CN120271996A
A bio-based high-flow mineral-reinforced PC / PET alloy material and its preparation method
CN120271996B